Pengaruh Profitabilitas, Leverage, dan Kepemilikan Institusional terhadap Tax Avoidance - Erlangga, Jimmy; sulestiyono, Deddy (Universitas Katolik Soegijapranata, Semarang, 2024)
Taxes are currently the largest source of government revenue in Indonesia. Legal efforts to reduce the tax burden in accordance with applicable regulations by using techniques or methods that take advantage of weaknesses in tax regulations and laws, is tax avoidance or what is called tax avoidance. The aim of this research is to test whether there is a relationship between profitability (ROA), leverage (DER) and institutional ownership on tax avoidance. In addition, the aim of this research is to determine whether there is a simultaneous relationship between profitability, leverage and company size and the level of tax avoidance. This research uses a purposive sampling method, a quantitative approach and uses secondary data by collecting data on manufacturing companies in the food and beverage sector for the 2017-2021 period on the IDX. This research used a sample of 125 data from 25 food and beverage manufacturing companies from 2017 to 2021. Analysis of the data used in this research was carried out using the Statistical Package for Social Science (SPSS) version 22. The results of this research prove that the level of profitability (ROA) has no effect on tax avoidance. The leverage ratio (DER) shows that leverage has a significant negative effect on tax avoidance and institutional ownership has a positive effect on tax avoidance and simultaneously profitability, leverage, institutional ownership have a significant positive effect on tax avoidance